Revision of the Nearctic species of Ditomyia Winnertz and a new species from the Neotropical Region (Diptera: Ditomyiidae) - Fitzgerald, Scott J. (Zootaxa, 2020)
The Nearctic species of Ditomyia Winnertz (Diptera: Ditomyiidae) are revised and four species are recognized: D. euzona Loew and D. potomaca Fisher from the eastern Nearctic and D. sohnsi n. sp. and D. elongata n. sp. from the western Nearctic. All species are figured and a key provided. Additionally, the first known Neotropical Ditomyia is described and the generic limits of Ditomyia discussed.